Publications and new products (Journal of EAHIL, 2024)
Dear all, for this issue’s “Publications and new products” column I’ve searched the web and selected news and articles regarding several current topics I hope would be of your interest. Among other news I’ve found on the web I would like to highlight some recent initiatives related to the switch towards prioritizing research quality over quantitative indicators when assessing research results.